Neuropathology and neuroinflammation in Alzheimer’s disease via bidirectional lung–brain axis - Lu, Jie; Li, Cheng-Jun; Wang, Jing; Wang, Yang (Frontiers in Aging Neuroscience, 2024)
Alzheimer’s disease (AD) is the most common form of age-related dementia worldwide. Although the neuropathology of AD is clear, its pathogenesis remains unclear. Recently, conceptualising AD as brain-centred has reoriented many scientists because the close functional relationship between the peripheral and central nerves is increasingly recognised. Recently, various studies have focused on the crosstalk between peripherals and centrals. A new hotspot of research and new therapeutic strategies have emerged from this great progress. This mini-review is an overview of the potential molecular mechanism in AD via the bidirectional lung-brain axis, providing a new perspective for the systemic understanding of AD onset.